Social Media Marketing and Performance of Small and Medium-Sized Enterprises in South West Nigeria - Isaac Olakunle Oludoyi; Isaac Adesuyi; Mofoluwake Folasayo Ayo; Samuel Mercy Buloere (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study examined the effect of social media marketing (Ad placement, content marketing, referral marketing, and influencer marketing) on performance (brand awareness, customer satisfaction, customer retention, and customer patronage) of Small and Medium-sized Enterprises (SMEs) in southwest Nigeria. The study also examined the moderating effects of trust on the performance of SMEs. The study adopted a cross-sectional research design, and employed multistage sampling techniques which included simple random, proportionate, and purposive sampling. A total of 383 owners/mangers of SMEs were selected in Ekiti, Ondo, and Oyo state. The findings revealed that social media marketing had significant positive effects on brand awareness, customer satisfaction, customer retention, and customer patronage. Furthermore, the findings revealed that trust had a significant moderating effect on performance of the selected SMEs. The study concluded that social media marketing had a significant effect of SMEs performance. The study recommended that SMEs should develop a comprehensive social media marketing strategy that encompasses various tactics such as influencer marketing, content marketing, referral marketing, and ad placement. These findings contribute to the understanding of the role of social media marketing in enhancing SMEs' performance in the specific context of Southwest Nigeria.